Social media content headlines and their impact on attracting attention - Kishokanth Jeganathan; Andrzej Szymkowiak (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2020)
Social media is an important source of product information for many users. Marketing in social media is based not only on building a community around the brand, but social media is used as a way to reach a defined group of users with a marketing message. These users are shown content, including promoted posts, which is to draw their attention, interest and get them to action, i.e. click on the link and read the article promoting an event or product. In this article, we investigated how the different headline wordings (question, traditional, forward referring) affect the desire to read the article. An experiment was conducted on 75 participants, which confirmed that the header has a large effect size. The ANOVA analysis was carried out in two stages, additionally taking into account the importance and general interest in the subject of the article by users. Finally, the possible business implications, limitations, and directions for future research were identified.
Keywords: D71; A14; D91; L82; 650; social media promotion; headlines; forward referencing; urge to read; content marketing